Hair dehydroepiandrosterone sulfate as biomarker of employees’ well-being? A longitudinal investigation of support, resilience, and work engagement during COVID-19 pandemic - Girardi, Damiano; Dal Corso, Laura; Arcucci, Elvira; Yıldırım, Murat; Pividori, Isabella; Prandi, Alberto; Falco, Alessandra (Frontiers in Psychology, 2024)
Building on the motivational process of the job demands-resources (JD-R) theory, in the current research we investigated the longitudinal association between supervisor support/resilience as job/personal resources, work engagement (WE) and hair dehydroepiandrosterone sulphate, or DHEA(S), as a possible biomarker of employees' well-being. In the context of the COVID-19 pandemic, 122 workers completed two self-report questionnaires (i.e., psychological data): the former at Time 1 (T1) and the latter three months afterwards, at Time 2 (T2). Participants also collected a strand of hair (i.e., biological data) at T2. Results from path analysis showed that both SS and resilience at T1 were positively related to WE at T2, which, in its turn, was positively related to hair DHEA(S) at T2. Both SS and resilience at T1 had a positive indirect effect on hair DHEA(S) at T2 through WE at T2, which fully mediated the association between job/personal resources and hair DHEA(S). Overall, results are consistent with the motivational process of the JD-R. Furthermore, this study provides preliminary evidence for the role of hair DHEA(S) as a biomarker of WE, a type of work-related subjective well-being that plays a central role in the motivational process of the JD-R, leading to favorable personal and organizational outcomes. Finally, the article outlines practical implications for organizations and professionals to foster WE within the workplace.